2016
DOI: 10.1063/1.4968037
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent density functional theory for the charging kinetics of electric double layer containing room-temperature ionic liquids

Abstract: Understanding the charging kinetics of electric double layers is of fundamental importance for the design and development of novel electrochemical devices such as supercapacitors and field-effect transistors. In this work, we study the dynamic behavior of room-temperature ionic liquids using a classical time-dependent density functional theory that accounts for the molecular excluded volume effects, the electrostatic correlations, and the dispersion forces. While the conventional models predict a monotonic inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 63 publications
(84 reference statements)
1
50
0
Order By: Relevance
“…TDDFT results further show that the dispersion interaction between ions makes the surface charge a non‐monotonic function of time (Figure b). However, the dispersion interaction between the electrode and ionic liquid does not change the monotonic evolution of surface charge density . Both the ion‐ion and the electrode‐ion dispersion interactions increase the duration of the EDL charging process .…”
Section: Edl Capacitance Inside Nanoporesmentioning
confidence: 94%
See 2 more Smart Citations
“…TDDFT results further show that the dispersion interaction between ions makes the surface charge a non‐monotonic function of time (Figure b). However, the dispersion interaction between the electrode and ionic liquid does not change the monotonic evolution of surface charge density . Both the ion‐ion and the electrode‐ion dispersion interactions increase the duration of the EDL charging process .…”
Section: Edl Capacitance Inside Nanoporesmentioning
confidence: 94%
“…However, the dispersion interaction between the electrode and ionic liquid does not change the monotonic evolution of surface charge density . Both the ion‐ion and the electrode‐ion dispersion interactions increase the duration of the EDL charging process . TDDFT was also used to examine ion conductance in nanochannels .…”
Section: Edl Capacitance Inside Nanoporesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for systems with oppositely charged particles, where the separation distance can be well below a nanometer, or for dense suspensions such a simple picture cannot be applied. A semi-analytical solution for interaction between nonuniformly but like-charged particles at an air-water interface has been recently provided which is valid at all separations between the particles [19]. An alternate approach, which makes the problem completely analytically solvable, is to use a relatively simple yet reasonable model system by ignoring the particle curvature and treating them as flat plates due to their short separation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in this case the linearization of the Poisson-Boltzmann (PB) theory is applicable [21]. Recent studies, directed towards the opposite limit of small inter-particle separations, have been performed within the linearized PB theory [22][23][24] or by considering a flat plate geometry [22,24,25] in order to simplify the problem. Whereas the former approximation is often violated at short separations, the latter represents the ideal situation of a contact angle of exactly 90 • and the absence of particle curvature.…”
Section: Introductionmentioning
confidence: 99%